Effect of pH, ultrasound frequency and power density on the release of calcein from stealth liposomes - Ahmed, Salma E. (2016)
The use of liposomes as carriers for chemotherapeutic agents in combination with ultrasound as a stimulus to control the time and space of the drug release is a promising approach for cancer treatment, as it can reduce the side effects caused by conventional chemotherapy. This in vitro study investigated the triggered release of calcein from stealth (PEGylated) and non-stealth (non-PEGylated) liposomes, using ultrasound at low (20 kHz) and high (1 and 3 MHz) frequencies, and at different power densities. Release was monitored by the increase in fluorescence due to relieving of calcein’s self-quenching upon dilution when the model drug leaks out of the liposomes. The results showed that, independent of the power density, the release was highest at 20 kHz. For the same frequency, release usually increased with increasing power densities. Additionally, for release at 20 kHz, a comparison was done for PEGylated and non-PEGylated liposomes, at two pH values: 5.2 and 7.4. The results were then compared to previously published studies. In all cases, the mechanism of release seems to involve cavitation events that either pierce a hole in or shear open the liposomes, as all the determined power densities are above the transient cavitation threshold.